Pengaruh Manajemen Talenta Terhadap Pengembangan Sumber Daya Manusia Di Era Digital - Dewi Puspaningtyas Faeni; Jumawan Jumawan; Alicia Angela Yohanas; Dinda Adelia; Elsa Santika; Nur Putri Cahyaningsih; Rani Rahmadiani; Nabella Nur Afiyah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Currently, globalization has entered the digitalization era, where digitalization has become one of the most important factors in organizational life. In recent years, there has been a steady increase in the use of technology in HR strategy and planning. This article explains how to apply talent management to develop human resources in this digital era. The method used in writing this article is using the literature review method, which searches databases from various reference sources such as journals, books and necessary data related to talent management. Effective talent management includes not only managing traditional human resources, but also focusing efforts on developing digital skills, identifying talent that fits digital initiatives, and creating a culture of innovation. Flexibility, mobility and giving employees greater responsibility have become important elements in successful talent management in the digital era. The use of technology also plays a key role in talent management with tools and data analytics that support better decision making. Regular evaluation and employee engagement are important aspects in ensuring successful talent management. Effective talent management will help companies remain competitive and ready to face ongoing technological changes.